The Effect of Lean Approach on Hospital Service Quality and Inpatient Satisfaction - Anton Timur Jailani Harahap; Chrismis Novalinda Ginting; Ali Napiah Nasution; Adek Amansyah (Unnes Journal of Public Health, 2023)
Measurement of the service quality is very important, especially to improve service quality and get loyal customers in a private hospital using a lean service approach. This research aims to determine the effect of a lean service approach based on variables including overproduction, waiting time, transportation, excess processing, inventory, motion and satisfaction defects. This study used a quantitative method approach with a cross-sectional design. The population were treated in the inpatient ward of Malahayati Hospital, Medan. The sample size was 110 patients, determined by Rao formula. The sampling technique was a purposive sampling technique with inclusion criteria of patients who were hospitalized for more than three days on March 2021. Data obtained were analyzed with the logistic regression tests. The results showed all variable have significant effect on the inpatient satisfaction including over production (p = 0.019), followed by waiting time (p = 0.012), transportation (p = 0.011), excess processing (p = 0.017), inventory (p = 0.010), motion (p = 0.015), and satisfaction defects (p = 0.010). Based on multivariate analysis concluded that hospital service quality affects inpatient satisfaction based on the waste inventory (4.567 times) as the highest and waste transportation (2.786 times) as the lowest. This study has strongly suggested that the hospital management should maintain over production waste and other waste variables in order to improve the service quality.